Optimism and teacher’s burnout - Terelak, Jan Felicjan; Mystkowski, Marek (Studia Psychologica: Theoria et praxis, 2010)
The work concems the opinions of degree of the teacher’s burnout, according to conception Christina Masłach, in report to optimism as factor the personality, in it understanding Michael Scheier and Charles Carter, modify this burnout. It in investigations the part took 98 teachers of schools over secondary-school. It to investigation of personal optimism the pessimism was applied was the Life Orientation the Test Revised the FLIGHT R Michael’s Scheier, Charles Carver and Michael Bridges (1994) in Polish adaptation Zygfryd Juczyński and the Ryszard of Poprawa. It teachers’ burnout to opinion was applied was Masłach Burnout Imentory MBI in Polish conducted by psychologists’ team under Helena’s Sęk management adaptation. It it was affirmed was that optimism in light of investigations is one with reactionary variables burnout professional in teachers’ Professional group, particularly in rangę the emotional exhaustion and reduced feeling of personal achievements.